On the design of active crossover network using double capacitive uniformly distributed RC filter - Wachirarattanapornkul, Sorapong; Tangsrirat, Worapong (My University, 2015)
This article presents the design of an active crossover network using double capacitive uniformly distributed RC filter (DURC). The proposed circuit includes the active DURC-based low-pass filter circuit together with the active high-pass filter circuit. The advantage property of this crossover network has flat magnitude response of crossover network signal and small phase difference. The proposed network also has low active and passive sensitivities. The simulation results by MATLAB and PSPICE in terms of the magnitude response, phase response, sensitivity and stability are approved the theoretical predictions.
Keywords: active filter; crossover network; DURC